Last of the Orang Utans ([S.l.] : Journeyman Pictures, 2003)
This video viewed the effort at Dutch primatologist, Wille Smith in tracking the task of saving some of the Orang Utan in Borneo from extintion.
Reporter, Jan Peter Lahpor ; videography, German E. Agravante
DVD format
Keywords: Orangutan -- Borneo (Sabah)